Wickerhamomyces anomalus in Mosquitoes: A Promising Yeast-Based Tool for the “Symbiotic Control” of Mosquito-Borne Diseases - Cappelli, Alessia; Favia, Guido; Ricci, Irene (Frontiers in Microbiology, 2021)
The ascomycete yeast Wickerhamomyces anomalus is a mutualistic symbiont of different insects, including diptera vectors of diseases. Although fungal symbioses have been so far poorly characterized, the topic is gaining attention as yeast-insect interactions can provide pivotal information on insect biology, such as their environmental adaptation or vectorial capability. We review the symbiosis between W. anomalus and mosquitoes, which implies nutritional and protective functions. Furthermore, we focus on antiplasmodial effects of W. anomalus in malaria vectors and discuss the yeast potential for the ‘symbiotic control’ of mosquito-borne diseases.